Tissue-preserving treatment with non-invasive physical plasma of cervical intraepithelial neoplasia—a prospective controlled clinical trial - Weiss, Martin; Arnholdt, Marcel; Hißnauer, Anna; Fischer, Irma; Schönfisch, Birgitt; Andress, Jürgen; Gerstner, Sophia; Dannehl, Dominik; Bösmüller, Hans; Staebler, Annette; Brucker, Sara Y.; Henes, Melanie (Frontiers in Medicine, 2023)
Cervical cancer represents the fourth leading cause of cancer among women and is associated with over 311,000 annual deaths worldwide. Timely diagnosis is crucial given the lengthy pre-cancerous phase, which is typified by cervical intraepithelial neoplastic lesions. However, current treatment methods are often tissue-destructive and can be accompanied by severe side effects. To address these concerns, our study introduces a novel, gentle approach for the tissue-preserving treatment of CIN lesions.We present findings of a controlled, prospective, single-armed phase IIb clinical trial performed at the Department for Women's Health, Tübingen, Germany. From 09/2017 to 03/2022 we assessed 570 participants for study eligibility. Of the screened patients, 63 participants met with CIN1/2 lesions met the inclusion criteria and were treated with non-invasive physical plasma (NIPP). Assessment of treatment efficacy was based on a comprehensive analysis of histological and cytological findings, along with high-risk HPV infection load at three and six months post-treatment. Comparative analyses were performed retrospectively with data obtained from 287 untreated patients in the control group. Our findings indicate that patients treated with NIPP experienced an 86.2 % rate of full remission, along with a 3.4 % rate of partial remission of CIN lesions, which compares favorably to the control group's rates of 40.4 % and 4.5 %, respectively. Additionally, we observed a twofold reduction in high-risk HPV infections following NIPP treatment. Minor side effects were observed, such as mild pain during treatment and short-term smear bleeding or increased vaginal discharge within 24 hours after treatment. Given the experimental nature of NIPP treatment and the availability of established standard treatments, our study was designed as a nonrandomized study.NIPP treatment offers a highly flexible and easy-to-apply method for treating pre-cancerous CIN1/2 lesions. This non-invasive approach is notable for its tissue-preserving nature, making it a promising alternative to current excisional and ablative treatments. CIN1/2 lesions were employed as preliminary in vivo models for the targeted treatment of CIN3 lesions.